Effects of upper and lower body wearable resistance on spatio-temporal and kinetic parameters during running. Issue 5 (2nd September 2020) - Couture, Grace A.; Simperingham, Kim D.; Cronin, John B.; Lorimer, Anna V.; Kilding, Andrew E.; Macadam, Paul
ABSTRACT: Wearable resistance training involves added load attached directly to the body during sporting movements. The effects of load position during running are not yet fully established. Therefore, the purpose of this research was to determine spatio-temporal and kinetic characteristics during submaximal running using upper, lower and whole-body wearable resistance (1–10% body mass (BM)). Twelve trained male runners completed eight 2-min treadmill running bouts at 3.9 m/s with and without wearable resistance. The first and last bouts were unloaded, while the middle 6 were randomised wearable resistance conditions: upper body (UB) 5% BM, lower body (LB) 1%, 3%, 5% BM and whole body (WB) 5%, 10% BM. Wearable resistance of 1–10% BM resulted in a significant increase in heart rate (5.40–8.84%), but minimal impact on spatio-temporal variables. Loads of 5% BM and greater caused changes in vertical stiffness, vertical and horizontal force, and impulse. Functional and effective propulsive force (2.95%, 2.88%) and impulse (3.40%, 3.38%) were significantly (p < 0.05) greater with LB5% than UB5%. Wearable resistance may be used to increase muscular kinetics during running without negatively impacting spatio-temporal variables. The application of these findings will vary depending on athlete goals. Future longitudinal studies are required to validate training contentions.